The cartoon guide to statistics - Gonick, Larry; Smith, Woollcott, 1941- (New York, NY : Collins Reference, 2005)
"The Cartoon Guide to Statistics covers all the central ideas of modern statistics: the summary and display of data, probability in gambling, and medicine, random variables, Bernoulli Trials, the Central Limit Theorem, hypothesis testing, confidence interval estimation, and much more- all explained in simple, clear, and yes, funny illustrations."-- (page 4) of cover
What is statistics? -- Data description -- Probability -- Random variables -- A tale of two distributions -- Sampling -- Confidence intervals -- Hypothesis testing -- Comparing two populations -- Experimental design -- Regression -- Conclusion
First published in 1993 by HarperResource
Includes bibliographical references (pages 221-223) and index
Keywords: Statistics -- Caricatures and cartoons; Sampling (Statistics) -- Caricatures and cartoons; Probabilities -- Caricatures and cartoons; Random variables -- Caricatures and cartoons; Economics -- Caricatures and cartoons